On the edges and in height. Socio-spatial contrasts in the diffuse growth of the Metropolitan Area of Mendoza (1990-2020) (Huellas, 2022)
In recent years, the Metropolitan Area of Mendoza (MAM) is among the Argentine cities that have grown the most in relation to its population increase. Different research works on this topic area agree on pointing out that over the last three decades the Great Mendoza area has shown an extensive and dispersed urban growth pattern which is producing a marked process of spatial fragmentation. This work aims at analyzing the spatial production modalities that explain the expansion of the MAM during the period 1990-2020, trying to reflect on the social processes related to them and the challenges that these changes imply for the study of the new ways of inhabiting the urban space. To this end, the first part presents an analysis of the mutations in the periurban landscape of Gran Mendoza, secondly there is a further analysis over the changes in the built environment in its central area. Thirdly, there is a review of the political and social factors that have been relevant for the current dynamism of the city. Finally, the paper presents the questions and analytical dilemmas facing the urban research regarding the approach to the different life fields that unfold through the metropolitan space of Mendoza.
Keywords: spatial fragmentation; urban inequality; urban sociability; Metropolitan Area of Mendoza